Keluhan Dermatitis Kontak Akibat Kerja pada Karyawan Pencucian Mobil Orbit Kota Semarang - Umi Novianti; Anik Setyo Wahyuningsih (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Contact dermatitis is skin inflammation that involves direct contact between the skin and toxic substances. The aim of this research is to find out the description of complaints of contact dermatitis in Orbit car wash workers in the city of Semarang. This type of research is observational analytic with a cross sectional design. The results of the research were that the most common complaints about the skin were itching (53%), skin blisters (53%), skin peeling (40%), redness (40%), swollen skin (20%), skin experiencing bumps. (47%), the skin experiences wrinkles (47%), the skin experiences cracking (20%) and small lumps filled with fluid (40%).